186k views
2 votes
Rewrite the logarithmic equation as an exponential equation: log27 3=1/3

2 Answers

2 votes

Answer:

3 = 27^1/3

Explanation:

log27 3=1/3

Raise each side to the base of 27

27^log27 3=27^1/3

3 = 27^1/3

User Alessmar
by
6.0k points
4 votes

Answer:


27^\left((1)/(3)\right)=3

Explanation:

Given logarithmic equation is


\log_(27)\left(3\right)=(1)/(3)

Question says to rewrite the given logarithmic equation as an exponential equation.

so we can apply transformation formula :


\log_(b)\left(c\right)=a => c=b^a

Using this formula, given problem can be transformed into exponential equation as:


\log_(27)\left(3\right)=(1)/(3) => {27}\left((1)/(3)\right)=3

Hence final answer is
27^\left((1)/(3)\right)=3

User Nickolayratchev
by
6.1k points